ERPs to nouns and verbs - congruences and differences - Petřek, Josef (Biomedical papers, 2004)
The results of the multivariate analysis of variance confirmed statistically significant differences in latency and amplitude of some ERPs waves to nouns and ERPs to verbs. ERPs to nouns differ from ERPs to verbs by a significantly longer latency and greater amplitude of some waves. A comparison of the characteristics of ERPs to nouns and ERPs to verbs separately in males and females produced basically identical results; in females, however, there are much fewer significant differences than in males. Interaction between the site of the recording electrode and features of ERPs to words of different word classes however could not be demonstrated.
Keywords: ERPs/Nouns/Verbs/Gender/Site of recording electrode